The use of pragmatic markers across proficiency levels in second language speech - Neary-Sundquist, Colleen (Zakład Filologii Angielskiej Wydział Pedagogiczno-Artystyczny Uniwersytetu im. Adama Mickiewicza w Kaliszu, 2014)
This study investigates the use of pragmatic markers (PMs) by learners of English at varying proficiency levels. The study analyzes data from a university-level oral proficiency exam that categorized Chinese and Korean English-as-a-second-language (ESL) speakers into four proficiency levels and compares data with those of native speakers taking the same test. Findings indicate that PM use generally rises with proficiency level. The rates of PM use showed a dramatic increase between the highest and second-highest proficiency group. The highest proficiency ESL group used PMs at the same rate as native speakers. The study also found that the variety of different PMs used goes up steadily with proficiency level. These results are discussed in terms of their implications for understanding how second language learners’ use of PMs develops.
Keywords: ragmatic marker; proficiency level; pragmatic competence; second language development; oral speech production